Cu(i)-Doped carbon quantum dots with zigzag edge structures for highly efficient catalysis of azide–alkyne cycloadditions. Issue 6 (30th January 2017) - Liu, Ze Xi; Chen, Bin Bin; Liu, Meng Li; Zou, Hong Yan; Huang, Cheng Zhi
Abstract : Cu(i )-CQDs with zigzag-shaped edges were prepared and used for a highly efficient catalysis of the Huisgen 1, 3-dipolar cycloaddition that was made possible owing to their rapid release of Cu(i ). Abstract : Photoluminescent (PL) carbon quantum dots (CQDs), in which Cu(i ) was doped stably owing to their specific zigzag edge structure, were used for catalyzing the Huisgen 1, 3-dipolar cycloaddition between azides and alkynes, the prototypical reaction of "click chemistry". The results showed the great potential of the as-prepared CQDs in catalysis chemistry applications.